European Industrial Doctoral School Summer Workshop 2019 - (:unkn) unknown (University of Pardubice, 2019)
This collection of book of abstracts was formed under the scope of the project INCENTIVE – Information Centre for Internationalisation of Research and Involvement in ERA, reg. No.: LTI17004. This project is financed by Ministry of Education, Youth and Sports of the Czech Republic.